The method of Christian theology : a basic introduction - Putman, Rhyne R. (Nashville, Tennessee : : B & H Academic, 2021)
Written for entry-level theology students, this book provides clear guidance for using theological sources, reasoning through difficult questions, and applying theological reflection in paper writing and preaching.
Introduction: Method matters -- Principles: Defining theology and its tasks -- Doctrine and truth -- Doctrine, worldview, and disciple-making -- The theological disciplines -- Preparations: A heart prepared for Christian theology -- A mind prepared for Christian theology -- Procedures: Scripture and its interpretation -- Tradition and Christian theology -- Philosophy and Christian theology -- Experience and Christian theology -- A procedure for theology -- Practices: Contextualizing doctrine -- Writing a theological research paper -- Preaching a doctrinal sermon.
Includes bibliographical references and index.
Keywords: Theology -- Methodology; Theology, Doctrinal; Theology, Doctrinal..; Theology -- Methodology..